Relative Effects of a Segmented Model versus a Combined Model in Teaching Appropriate Group Discussion Skills to Children - Borgen, W. A.; Calder, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to compare the effectiveness of two different modeling strategies in teaching group discussion skills to grade two students. More specifically, the study investigated whether it was more effective to model a complex behavior (appropriate group discussion) as a unit to break it into a series of segmented component parts (sticking to the point, self-disclosing, and listening). It was found that the segmented treatment was significantly more effective than the control group treatment regarding all three skills while the combined modeling treatment was only significantly better than the control on the listening variable. Findings were discussed in terms of developing strong modeling packages to teach a variety of skills.